Urban heat island and thermal comfort of Esfahan City (Iran) during COVID-19 lockdown. (10th June 2022) - Roshan, Gholamreza; Sarli, Reza; Fitchett, Jennifer M.
Abstract: The Urban Heat Island (UHI), driven in part by urban green space transformation, and resulting in bioclimatic stress, is one of the major environmental problems facing cities today. A brief reprise in UHI severity is hypothesised to have occurred for many cities during COVID-19 lockdown, as a result of the marked reduction in individual and industrial activities. This study explores the UHI the city of Esfahan, one of the major metropolises of Iran, comparing the urban temperature for the period 20 March to 20 April 2020, the first lockdown period in Iran, with a long term mean for this month calculated from 2000 to 2019. During the lockdown period, the UHI effect covered a much smaller land area than in all prior years investigated. The land surface area which experienced heat stress reduced significantly during the lockdown period, and the total energy heating requirement (heat degree days) increased by 23, 945.2° day calories compared to the long term average. These results demonstrate the significant changes in UHI and related variables during lockdown. While lockdown regulations are not sustainable in the long run, the improvements recorded demonstrate the potential to mitigate anthropogenic heating. Graphical abstract: Image 1 Highlights: COVID-19 lockdown resulted in reduced pollution and anthropogenic heating globally with the suspension of industrial activities. This has the potential to reduce the intensity and land surface area of urban heat islands, and alleviate the reliance on cooling energy. We explore changes in the UHI size, position and intensity, and cooling and heating requirements for Esfahan City. Statistically significant decreases in temperature for 2020 relative to 2000-2019, increased heating energy requirements.